2017
DOI: 10.12693/aphyspola.132.1552
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation Studies of the Free Volumes in Nylon12/PVA Films Treated by Supercritical Carbon Dioxide

Abstract: Free volume variations of Nylon12/Polyvinyl alcohol (Nylon12/PVA) blends treated in supercritical carbon dioxide (ScCO2) were investigated using positron annihilation lifetime spectroscopy. It is found that o-Ps lifetime τ3 and the corresponding intensity I3 in Nylon12/PVA decrease with increase of the PVA content. Being treated in ScCO2 at 50• C and 20 MPa for 1 h, the free volume holes in Nylon12/PVA blends expand to different extents depending on the weight ratio of PVA. After releasing of CO2, the free vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The free volume of blends Nylon12/PVA, treated with supercritical CO 2 , was studied using PALS [ 108 ]. Lifetime and intensity of o-Ps decrease with increasing content of PVA with respect to neat Nylon12, which is attributed to the higher crystallinity of PVA as well as the extra intermolecular hydrogen bonding between Nylon12 and PVA, acting as physical crosslinks that reduce the molecular mobility of Nylon12 and the free volume sizes.…”
Section: Discussion Of Some Pals Results In Polymeric Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The free volume of blends Nylon12/PVA, treated with supercritical CO 2 , was studied using PALS [ 108 ]. Lifetime and intensity of o-Ps decrease with increasing content of PVA with respect to neat Nylon12, which is attributed to the higher crystallinity of PVA as well as the extra intermolecular hydrogen bonding between Nylon12 and PVA, acting as physical crosslinks that reduce the molecular mobility of Nylon12 and the free volume sizes.…”
Section: Discussion Of Some Pals Results In Polymeric Systemsmentioning
confidence: 99%
“…The solid lines represent the fitting relaxation curves of the three samples (reproduced from ref. [ 108 ] with permission from Acta Physica Polonica A. DOI: 10.12693/APhysPolA.132.1552).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The positron annihilation lifetime fundamentals will be discussed in the second section. Li et al [ 18 ] concentrated on the free-volume varieties of Nylon-12/PVA melt-blends treated in supercritical carbon dioxide (ScCO 2 ) using PAL spectroscopy. They found that the free volume opening size and its items declined with the increment in PVA content.…”
Section: Introductionmentioning
confidence: 99%